Experiments with Truth : Narrative Non-Fiction and the Coming of Democracy in South Africa. - Twidle, Hedley (African Articulations Ser., 2019)
Unusable pasts; scandalous lives; political betrayal, confession and collaboration: reading narrative non-fiction across South Africa's unfinished transition.